The Transformation of Educational Management in the Disruption Era - Herman Herman (Institut Agama Islam Negeri Padangsidimpuan, 2021)
This article describes the transformation of educational management in the disruption era. It could encourage school’s staff and other stakeholders to make improvements, changes, and innovations from traditional or manual systems to digitalization systems such as the MOOC (Massive Open Online Course) application and AI (Artificial Intelligence) which could create convenience, relief, and acceleration of improving the quality of educational program. This study used qualitative method with descriptive approach through library research. The writing technique was carried out through several stages started from the data collection stage to data processing and analysis stage that was considered relevant and had relationship with the problems of the study. Based on the result, it shows that the transformation of educational management in the disruption era includes: 1) transforming educational management that is centered on the achievement of service quality and graduates, 2) leadership which has vision and mission that create concrete and transparent policies, 3) organizing the human resources who are capable of making improvements, changes and innovations, and 4) building a work culture that produces and generates the indicators of performance.